Electrophoretic deposition of (Zn, Nb)SnO2-films varistor superficially modified with Cr3+. Issue 7 (July 2015) - Lustosa, Glauco Meireles Mascarenhas Morandi; da Costa, João Paulo de Campos; Perazolli, Leinig Antônio; Stojanovic, Biljana D.; Zaghete, Maria Aparecida
Abstract Recently, there has been an important rise in the research and development aimed to improve the properties of SnO2-based varistors. Meanwhile, due to fact that ZnO-based varistors possess better electrical properties compared to SnO2-based varistors, it is shown that it is needful to add additives to improve their properties. In our study, the SnO2-powder was prepared by the chemical route (Pechini method) with addition of ZnO (1 mol%) and Nb2O5 (0.05 mol%). Films were obtained by the electrophoretic deposition of SnO2-based powder, following by microwave oven sintering. Cr3+ was deposited by EPD on the films surface and thermal treatment was carried out in a microwave oven. After electrical characterization the films showed nonlinear coefficient over 10, breakdown voltage around 60 V, low leakage current (≈10−6 A) and resistance over 200 kΩ cm. This indicates the efficiency of the used techniques to prepare varistor films with improved electrical properties after Cr3+ diffusion.